Influence of transition metal electronegativity on the oxygen storage capacity of perovskite oxides. Issue 68 (1st August 2016) - Liu, Lu; Taylor, Daniel D.; Rodriguez, Efrain E.; Zachariah, Michael R.
Abstract : The selection of highly efficient oxygen carriers (OCs) is a key step necessary for the practical development of chemical looping combustion (CLC). Abstract : The selection of highly efficient oxygen carriers (OCs) is a key step necessary for the practical development of chemical looping combustion (CLC). In this study, a series of ABO3 perovskites, where A = La, Ba, Sr, Ca and B = Cr, Mn, Fe, Co, Ni, Cu, are synthesized and tested in a fixed bed reactor for reactivity and stability as OCs with CH4 as the fuel. We find that the electronegativity of the transition metal on the B-site ( λ B ), is a convenient descriptor for oxygen storage capacity (OSC) of our perovskite samples. By plotting OSC for total methane oxidation against λ B, we observe an inverted volcano plot relationship. These results could provide useful guidelines for perovskite OC design and their other energy related applications.